Does financial assistance (GKP) for SMEs-during the Covid 19 pandemic, help to improve their survivability and sustainability? - Razi, Nor Faezah Mohamad; Sarkam, Nor Aslily; Mohammad, Nor Hazlina; Nasaruddin, Nur Hasni; Ahmad Junid, Rosida (Technium Social Sciences Journal, 2022)
Nations require small and medium-sized enterprises, also known as SMEs, to perform well in order for their economies to advance from the middle-income bracket to the high-income bracket. However the global pandemic has had a significant impact on SME business owners, who face various trade challenges and have been forced to change their business models in order to adapt to this situation. Some of them have succeeded, but some have had to close their businesses. These economic changes have contributed to a direct reduction in the employment rate in Malaysia. In recognition of the need for strong Malaysian communities, a special grant known as the Geran Khas Prihatin (GKP) was created by the government to help SMEs survive in the post-Covid 19 environment. This assistance was granted to qualifying SMEs who requested aid and who met the necessary requirements. However, we must ask if this financial aid was indeed able to help the SMEs in the Hilir Perak district to sustain their businesses based on measures of Satisfaction, Perceived Expectation, Perceived Value, and Motivation. Methodologically, questionnaires were the instrument tool which was used and they were distributed via face-to-face interviews in the Hilir Perak district. The researchers were able to gather 180 different SME owners to participate in this study. Structural Equation Modelling (SEM) was applied to measure the success or failure of the current approach in helping SME business owners to survive during the pandemic by considering the four main factors, which are: Satisfaction, Perceived Value, Perceived Expectation, and Motivation. The results revealed that 92.8% of respondents heard about GKP and 83.9% applied for GKP, but only 79.4% of the respondents succeeded in obtaining the assistance. On average, the amount of GKP received by the respondents was RM3702.33. Meanwhile SEMs revealed that based on the Motivation (endogenous) attribute, it can be concluded that most of the recipients are happy for the help of the GKP program in maintaining their business, and like when people praise the success of their business during the Covid 19 pandemic.